TRUTHFUL IS MORAL: PRACTICING ETHICAL RESPONSIBILITY IN CHINESE HISTORIOGRAPHY. - Wang, Q. Edward (History & Theory, 2024)
In recent years, efforts have been made to reevaluate the tradition of Chinese historical thought and writing. This article seeks to further these efforts and offer a new understanding of the characteristics of historical writing in traditional China. It argues that, at the level of practice, traditional Chinese historians, like their counterparts in the rest of the world, were deeply concerned with establishing and communicating facts in historical writing. Their separation of commentary and narrative in order to practice "straight writing" of the latter is a telling example, one that evolved into an enshrined tradition over the long span of imperial China. At the theoretical level, Chinese historians also consciously explored the ways in which truthfulness in history could be reconciled with the ethical responsibilities they perceived and sought to assume in and for their time. This quest did not stop at the level of "praise and blame" for past personalities and events. Rather, their practice amounted to an effort, epitomized by the historical practice of the Song period (960–1279), to search for the metaphysics of historical morality, or the immanent and overarching principles that guide human society.